To Determine the Measles Vaccination Status and its Correlates in Children with Measles (Medical Forum Monthly, 2024)
Objective: To assess the measles vaccination status of children with measles and to ascertain the reason for any omission.Study Design: Descriptive / case series studyPlace and Duration of Study: This study was conducted at the Pediatric Unit, Rehman Medical Institute, Peshawar from January 2013 to December 2013.Materials and Methods: Sixty children with measles according to CDC clinical criteria were included. Data regarding the demographics and immunization status was noted after consent. The children who were vaccinated against measles were enquired about the history of contact and the ones not vaccinated, about the reason for omission.Results: Out of 60 patients 36 (60 %) were male and 24 (40%) were females.52 (86.6%) were Pakistani while 8(13.3%) were Afghani. 31(51.6%) were between 3-12 months ,those aging between 13-24 months were 8(13.3%) while ages 3-7 years and above 7 years were 16(26.6%) and 4(6%) respectively. Only 12 (20%) were vaccinated according to the EPI schedule including measles vaccine, out of these 7gave history of contact .Twelve (20%) were not vaccinated at all against any of the infectious diseases including measles because of lack of awareness or unavailability of vaccines while36 (60%) were vaccinated according to EPI schedule but measles vaccination was not done either due to age less than 9 months or lack of awareness about measles vaccine.Conclusion: Measles outbreaks will continue unless awareness and immunization rates are increased and maintained at universal levels.